The development and evolution of the Burdekin River estuary freshwater plume during Cyclone Debbie (2017). (31st August 2019) - Xiao, Yuanchi; Wang, Xiao Hua; Ritchie, Elizabeth A.; Rizwi, Farhan; Qiao, Lulu
Abstract: This paper investigates the plume morphology and dynamics prior to and after the landfall of Cyclone Debbie (2017). The heavy rainfall and flooding produced a large buoyant coastal current, which moved southward after the cyclone landfall then advected northward with the prevailing southerly wind. The plume is simulated using the eReef GBR1 1-km model and a passive tracer is used to identify the plume behaviour. Based on the concentration of river tracers from the Burdekin River, the plume had propagated over 100 km to the north 23 days after the cyclone landfall. Based on an Empirical Orthogonal Function (EOF) analysis, the cyclone-induced river discharge is found to be the major cause for surface salinity variation with a lag time equal to 17 h. The response of surface plume area to the river flow is about 40 h lag with correlation coefficient = 0.68 and according to the wind strength index, the plume was controlled by buoyancy on c1 but could be controlled by wind in the far field. Wind also plays a very important role. Under weak downwelling wind forcing lower than 0.1 Pa, the plume thickness is sensitive to river discharge and tides. With stronger downwelling wind forcing larger than 0.1 Pa vertical mixing is generated, the plume is restricted to the coast, and high river discharge can only affect the thickness of the plume, but not its width. After Cyclone Debbie made landfall, upwelling winds developed, and the freshwater plume reversed direction from northward to southward most likely due to the influence of the northerly wind as well as the ambient current and topography.